Pathology tests: is the time for demand management ripe at last?. Issue 4 (1st April 2003) - Gopal Rao, G; Crook, M; Tillyer, M L
Abstract : With the ever increasing demands for pathology testing within the National Health Service there is a need to manage the demand for these tests. This review discusses strategies for the demand management of requests made by clinicians in the disciplines of biochemistry, haematology, and microbiology. The various approaches that have been used to manage demand will be described, along with specific clinical strategies for demand management.